Riparian buffer management through time in the Krycklan catchment : has the composition in riparian zones been affected by previous management since 1963? - Larsson, Linnéa; Nygårdh, Julia (SLU/Dept. of Forest Ecology and Management, 2020)
Ecosystem services and many conflicting interests make management of small streams in the forest an important topic. Streams need to be protected in a way that maintains water quality, quantity and riparian characteristics. In 2013 the Swedish Forest Agency presented new Strategic Management Objectives (SMOs or “målbilder”), that included directives for protecting streams in the forest by better management of riparian zones and creation of buffers. The aim of this study was to determine how past forest management has affected riparian zones. The data was collected within the Krycklan Catchment Study area in Vindeln, Västerbotten County, Sweden in autumn of 2019. Characteristics of the riparian zones, such as species richness of woody plants and the presence of stumps, were inventoried and have been analysed both over time and at different distances from the stream. Additionally, a subjective visual analysis of aerial photos (from 1963 to 2013) and a measure of the buffer width left after a harvest were made. The results showed a connection between both species richness of all woody plants and deciduous species related to distance from stream and age class. Presence of stumps for deciduous trees decreased over time. There were also differences in riparian buffer width over time. It was difficult to see a correlation between past forest management and the components inventoried in riparian zones. The changes in the Forestry Act in 1993 could have had some effect on the protection of streams. The SMOs from 2013 have not yet had an effect on riparian zones.